Sharkification - De Middel, Cristina 1975- (Editora Madalena, 2016)
The artist depicts the "favelas" of Brazil as a coral reef where the battle between the police and drug gangs can be seen as sharks in pursuit of small fish
Keywords: De Middel, Cristina / 1975-; Photography, Artistic; Photography / Brazil; Documentary photography / Brazil; Rio de Janeiro (Brazil) / Social conditions / Pictorial works; Documentary photography; Photography; Social conditions; Brazil; Brazil / Rio de Janeiro; Photobooks; Pictorial works